2019
DOI: 10.1002/anie.201902377
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of H‐Bonds with Aromatics in Isolated Complexes Identifies Isomeric Carbohydrates

Abstract: The tremendous isomeric diversity of carbohydrates enables awide range of their biological functions but makes the identification and study of these molecules difficult. We investigated the ability of intermolecular interactions to communicate structural specificity of carbohydrates to protonated aromatic molecules in non-covalent complexes,i solated and cooled in the gas phase.Our study revealed that small structural differences between carbohydrate isomers of any type,i ncluding enantiomers,a re accurately c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…The isomeric structure of a guest carbohydrate is communicated to the host aromatic molecule by noncovalent interactions, which induce changes in the UV absorption of the latter. In particular, an interplay of different types of H-bonds in isomeric complexes make the position of their UV absorption onset very sensitive to the isoform of a guest carbohydrate . We also found that the number of low-energy conformers is much lower for noncovalent complexes of glycans with aromatic molecules than for glycan–alkaline ion adducts, , which are often used for identifications of isomeric carbohydrates by IR spectroscopy.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…The isomeric structure of a guest carbohydrate is communicated to the host aromatic molecule by noncovalent interactions, which induce changes in the UV absorption of the latter. In particular, an interplay of different types of H-bonds in isomeric complexes make the position of their UV absorption onset very sensitive to the isoform of a guest carbohydrate . We also found that the number of low-energy conformers is much lower for noncovalent complexes of glycans with aromatic molecules than for glycan–alkaline ion adducts, , which are often used for identifications of isomeric carbohydrates by IR spectroscopy.…”
mentioning
confidence: 70%
“…2D UV-MS fingerprinting is a recently developed approach that is capable of highly accurate identification of isomeric biomolecules. [17][18][19][20][21][22] This analytical technique integrates UV photofragmentation (UVPD) spectroscopy of cryogenically cooled ions with broadband highresolution (e.g. Orbitrap-based) mass spectrometry.…”
mentioning
confidence: 99%
See 3 more Smart Citations